Exchange by hydrogen and deuterium through the interface of contacting metals; Journal of surface investigation: X-ray, synchrotron and neutron techniques; Vol. 16, N 5 - Chernov I. P. Ivan Petrovich (2001, 2001)
В фонде НТБ ТПУ отсутствует